Argumentacja ex auctoritate w uzasadnianiu twierdzeń w tekstach homilii - Klementowicz, Michał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
Each public speech (including the homily) should be associated with showing the right which serves as the basis for accepting the presented statements. This is one of the fundamental features of the correct construction of a statement. The theological content of a homily can be presented on the basis of the classical form of argumentum ex auctoritate. As an inductive structure, this argument may promote specific ways of organising the whole speech. Firstly, in the rhetorical inventio structure, it allows the author to control the semantic coherence of the text. Secondly, in the structure of dispositio, the authority can make for an interesting use of rhetorical narrative in homily text. Thirdly, argumentum ex auctoritate can be used to build the ethos of the preacher. Thanks to the above proposals, it is possible to influence the processuality of the text, which may determine the recognition and assimilation of the different key elements, both of which are crucial for preaching.